The Role Of Standard Form Contracts In An Information Society And ‘Smart Contract’ Furture - Cornelius Way, Kristin (AoIR Selected Papers of Internet Research, 2017)
A common feature of commercial relationships, standard-form contracts (SFCs) have been a product of organized commerce in some fields (e.g. marine shipping, banking) for many centuries, and in others (e.g. mass production industries) more recently as a modern form of a business service contract for consumers. Modern SFCs have many positives; they encourage trade by increasing transactional efficiency, being used in multiple, repeated events for a broad range of consumers and presented on a ‘take-it-or-leave-it’ basis without negotiation, significantly decreasing transaction costs. However, SFCs have also been questioned for their potential abuses as, by their nature, they leave one party (i.e. the adherent, or the entity who is being served) subject to the will of the other (i.e. the drafter, or the entity providing the service). Given the increasing pervasiveness of the SFC in the digital environment, we must now ask ourselves how SFCs function in an networked, information society, as well as to consider possible solutions that may provide more transparency of their context and affordances. This project develops an articulated theory regarding the role of SFCs through an analysis of two case studies—a sample of Terms of Service (ToS) agreements from popular platforms and a look toward the future of SFCs as they might exist with ‘smart contract’ technology that makes use of distributed ledger technology and can potentially encourage a lucrative market of SFCs in a networked world.